Postmortale Untersuchungen an der Europäischen Wildkatze (Felis silvestris silvestris SCHREBER, 1777) - Steeb, Sandra; Justus Liebig University Giessen (My University, 2015)
Hundert Totfunde von Europäischen Wildkatzen aus Deutschland und Luxemburg wurden morphologisch, morphometrisch, pathologisch, virologisch, bakteriologisch und parasitologisch untersucht. Die Haupttodesursache war mit 84 % der Verkehrstod, daher entspricht der pathologische Teil in weiten Teilen einer Trauma-Studie. Todesursächliche Infektionen standen mit 5 % an zweiter Stelle (Salmonella enterica, E. coli, Erysipelothirix rhusiopathiae, Streptococcus dysgalactiae und Felines Parvovirus). Eine FeLV-Infektion war bei drei Wildkatzen als Kofaktor am Krankheitsgeschehen beteiligt. Außer dem FIV kommen alle für Hauskatzen relevanten Erreger von Infektionskrankheiten in der Wildkatzenpopulation vor (serologisch positiv waren für FHV 16 %, FCV 15 %, FPV 33 %, FeLV 18 % und für Chlamydophila sp. 6 %). Die Parasitenfauna der Wildkatze entspricht weitgehend derjenigen der Hauskatze mit einer hohen Prävalenz von Toxocara cati (91 %) und Taenia taeniaeformis (81 %). Bei 12 % der Wildkatzen wurde Cylicospirura petrowi nachgewiesen, ein Spiruride, der parasitäre Granulome im Magen verursacht. Echinococcus multilocularis war bei 5 % mit immaturen Individuen vorhanden. Molineus sp., Troglostrongylus brevior und Angiostrongylus sp. wurden zum ersten Mal bei (Wild-)Katzen in Deutschland nachgewiesen. Die Arbeit zeigt den aktuellen Status der Wildkatzenpopulation bezüglich veterinärmedizinisch wichtiger Kriterien (Reproduktion, Krankheitsgeschehen, Parasiten) an einer vergleichsweise großen Stichprobenanzahl und erfüllt damit die Vorgaben der FFHRichtlinie. Sie schafft Vergleichsmöglichkeiten für nachfolgende Untersuchungen und gibt Ansätze für weitere Untersuchungen.

A morphological, morphometrical, pathological, virological, bacteriological and parasitological investigation was performed with one hundred carcasses of the European wildcat found in Germany and Luxembourg. The main cause of death was road kill (84 %), which is why the pathological findings are mainly comprised of traumatic injuries. Infections leading to death were in the second position (5 %), with the causative agents Salmonella enterica, E. coli, Erysipelothirix rhusiopathiae, Streptococcus dysgalactiae and FPV. In three wildcats, FeLVinfection was a cofactor in the disease process. With the exception of the FIV, all important infectious agents of domestic cats were present in the wildcat population (serologically positive for FHV 16 %, FCV 15 %, FPV 33 %, FeLV 18 % and for Chlamydophila sp. 6 %). The parasite fauna is generally identical with the one of the domestic cat. There was a high prevalence of Toxocara cati (91 %) and Taenia taeniaformis (81 %). Cylicospirura petrowi was detected in 12 % of the wildcats; this spirurid causes parasitic granulomas in the gastric wall. Echinococcus multilocularis was present with immature individuals in 5 % of the investigated wildcats. Molineus sp., Troglostrongylus brevior and Angiostrongylus sp. were described for the first time in (wild)cats from Germany. The study reveals the current state of the wildcat population with regard to criteria important for veterinary medicine, such as reproduction, diseases and parasites. Due to these interdisciplinary results and the comparatively high sample size, the requirements of the FFHDirectives are achieved. Future surveys can be compared with this study and approaches for further investigations are proposed.
Keywords: ddc:630